Towards a universal implementation of labor companionship: a synthesis of the policy and facility environment of eight low-and-middle income countries - Soha El-Halabi; Andrea Barnabas Pembe; Alexandre Dumont; Ana Pilar Betrán; Charles Kaboré; Effie Chipeta; Guillermo Carroli; Helle Mölsted Alvesson; Hussein Kidanto; Jean-Paul Dossou; Kristi Sidney Annerstedt; Lenka Beňová; et al. (Frontiers in Health Services, 2025)
BackgroundLabor companionship, the presence of a woman's person of choice during childbirth, has benefits to both woman and baby and is recommended by the World Health Organization since 2012. However, implementation remains sub-optimal, especially in low-and-middle-income countries (LMICs). This study aimed to understand the maturity of labor companionship implementation in eight low-and-middle income countries with focus on the policy and facility environment.MethodsThis was a multi-country study nested in two hospital-based implementation research studies: Action Leveraging Evidence to Reduce perinatal mortality and morbidity in Sub-Saharan Africa (ALERT) study and the QUALIty DECision-making by women and providers for appropriate use of caesarean section (QUALI-DEC) study. We included 48 hospitals from eight countries: Argentina, Burkina Faso, Thailand and Viet Nam (QUALI-DEC) and four from each of Benin, Malawi, Tanzania and Uganda (ALERT). We used data from (i) a document review, including national policy documents and (ii) health facility readiness assessment, including physical layouts of maternity wards, all collected between December 2019 and April 2021. Our analysis included two steps, (1) a structured data abstraction with coding to pre-defined categories to analyse the national polices and available resources on a facility level which informed the (2) categorization of implementation maturity in three implementation phases modelled by the framework by Bergh et al. and the logic model developed by Bohren et al.ResultsThree of the eight countries lacked any national-level companionship policies, four had some mentioning and only one had detailed guidance on roles of labor companions and implementation guidelines. The physical outlines of maternity wards varied greatly, and lack of space was one of the main implementation barriers to all countries except Argentina. We classified Benin, Thailand and Viet Nam in the pre-implementation phase because of missing guidelines and limited implementation; Burkina Faso, Malawi, Uganda and Tanzania in the early implementation phase; and Argentina in the institutionalization phase where policies and facility resources were conducive.ConclusionSuccessful implementation was supported by concrete and contextualized implementation guidance. To move to high implementation levels, supporting policies, guidelines and structural changes in the maternity wards are needed.